The association between active and passive tobacco smoke exposures and epilepsy in United States participants of the National Health and Nutrition Examination Survey (2013–2018) - Tingting Song; Chunlan Jia; Qi Wang; Jie Mu; Jie Mu (Frontiers in Neurology)
BackgroundEpilepsy is a common chronic neurological disease, and identifying modifiable risk factors for epilepsy and seizure is extremely important. Currently, the relationship between tobacco exposure and epilepsy or seizure is controversy.ObjectiveThe objective of this study is to test the relationship between tobacco smoke exposures and epilepsy in United States (US) participants of the National Health and Nutrition Examination Survey (NHANES).MethodsThis is a cross-sectional study using data from NHANES 2013–2018. We included all participants in these cycles and excluded those with missing variables. Weighted logistic regression models, weighted sensitivity analysis and weighted subgroup analysis were conducted to estimate the association between active and passive tobacco smoke exposures and epilepsy.ResultsWe included 15,277 participants in NHANES, of whom 131 reported with epilepsy [taking at least one antiseizure medication (ASM) for epilepsy and recurrent seizures]. The weighted mean age of individuals is 42.35 years, 49.08% (95% confidence interval [CI] 48.03–50.12) were male, 64.56% (95%CI 63.70–65.41) were Non-Hispanic White, and 59.95% (95%CI 58.98–60.92) were private insurance. The weighted prevalence of epilepsy was 0.82% (95%CI 0.60–1.11) and 0.60% (95%CI 0.42–0.86) in those with and without tobacco smoke exposures, respectively. After adjusting for covariates, active and passive tobacco smoke exposure was not associated with epilepsy [weighted adjusted odd ratio (OR) 1.16, 95% CI 0.68–1.98, p-value = 0.576] and the results remained in multiple sensitivity analyses. However, we found that tobacco exposure was a protective factor for epilepsy in those aged 40–50 (OR 0.23, 95%CI 0.10–0.53, p-value < 0.001).ConclusionIn summary, tobacco exposure was not associated with epilepsy in the US population and this result remained after adjusting for confounding factors, and the sensitivity analysis was robust. However, in stratified analysis, tobacco exposure was a protective factor for epilepsy patients aged 40–50.